A MPB entre o nacional, o popular e o universal: Edu Lobo e Caetano Veloso, engajamento político e atualização musical em debate (1965-1968) - Martins, Eder (2008)
This dissertation is making an analyze of the relation established between the proposals of cultural intervention and musical creation of Edu Lobo e Caetano Veloso with the matter of the politician involvement artist and the musical up to date during 1965 and 1968. To leave of this, the project identify that the both artists had defined, by his musical creations, specify synthesis regarding the popular and cosmopolitan cultural references, whereas they prepared, during the conflict between MPB and Tropicália, different up to date projects for the popular brazilian musical. Besides, it was possible to find out the singular dialogue conceived by the proposals of cultural intervention of the Edu Lobo and Caetano Veloso with the theoretical and literary production of the modernity authors, such as, Mário de Andrade e Oswald de Andrade